The Supply Function Equilibrium and Its Policy Implications for Wholesale Electricity Auctions - Pär Holmberg; David Newbery (Research Institute of Industrial Economics (IFN), 2009)
The supply function equilibrium provides a game-theoretic model of strategic bidding in oligopolistic wholesale electricity auctions. This paper presents an intuitive account of current understanding and shows how welfare losses depend on the number of firms in the market and their asymmetry. Previous results and general recommendations for divisible-good/multi-unit auctions provides guidance on the design of the auction format; setting the reservation price; the rationing rule; and restrictions on the offer curves in wholesale electricity auctions.
Keywords: C62; D43; D44; L94; 330; Wholesale Electricity Markets; Supply Function Equilibria; Competition Policy; Elektrizitätswirtschaft; Regulierung; Wettbewerbspolitik; Oligopol; Auktion; Spieltheorie; Allgemeines Gleichgewicht